Considerations for Commercial Plant Introduction From Public Gardens - Matthew Taylor (Sibbaldia, 2017)
Public gardens can benefit from the introduction of new plants to the horticulture industry. There are many ways to develop and discover new plants in the public garden setting, whether it be through plant breeding, exploration or simply discovering a sport or mutation. The characteristics of plants suitable for the commercial display industry include short time to flower, no day-length requirement, easy and fast propagation, natural branching and inherent short height. Over the last 20 years, the process of plant development and introduction has changed enormously. Now, elements such as strong brands and marketing campaigns, plant patents or plant breeders’ rights, trademarks and the ability of a new plant to thrive in mass production settings are important considerations when making a new plant release. In addition, public gardens must evaluate potential commercial partners to ensure that they get the maximum benefits from the process. This paper describes that process and gives recommendations for some of the key stages with reference to plants released by Longwood Gardens in Philadelphia.